Juridical and Microeconomic Analysis of Franchise Agreements as Business Investment Instruments - Moh. Ja’far Sodiq Maksum; Wisnu Mahendri (Business Management Research, 2025)
Franchise agreements are modern business instruments that integrate legal, economic, and ethical aspects within a unified framework of partnership. This study aims to analyze the juridical aspects and microeconomic approach to franchise agreements in Indonesia, using a case study of the agreement between PT Indomarco Prismatama (Indomaret) and its partner. Employing a normative juridical approach and descriptive qualitative analysis, the study finds that franchise agreements are legally valid but often unilateral and marked by an imbalance of contractual power. From an economic perspective, the distribution of incentives and risks remains inefficient and inequitable. Furthermore, the implementation of business ethics remains challenging, particularly in terms of transparency and franchisor's social responsibility toward franchisees. This study recommends policy reform, fairer contract design, and strengthening legal capacity among franchisees to foster a more balanced and sustainable business partnership.